Thermal imaging for microvascular free tissue transfer monitoring: Feasibility study using a low cost, commercially available mobile phone imaging system. Issue 10 (6th July 2020) - Meyer, Annika; Roof, Scott; Gray, Mingyang L.; Fan, Caleb J.; Barber, Brittany; Miles, Brett A.; Teng, Marita; Genden, Eric; Rosenberg, Joshua D.
Abstract: Background: The use of infrared thermography to evaluate the perfusion of tissue flaps have been studied. This study aims to evaluate the utility of thermal imaging for flap monitoring with a low‐cost, readily available smartphone imaging device. Methods: Adult subjects who underwent head and neck reconstruction using a microvascular free flap with a cutaneous paddle were recruited. Thermal images were taken of the free flap before, during and after anastomosis. Thermal images were analyzed by measuring the average flap temperature minus the average surrounding tissue temperature (dT). Results: Twenty‐one patients were enrolled. The mean dT for flaps intraoperatively prior to anastomosis was −11.47 °F. For 20 patients, dT averaged between −0.30 to 0.12 °F. One flap was inadequately perfused and dT was found to be −4.35 °F. Conclusions: Low cost, mobile smartphone devices such as the thermal camera may provide an objective method of monitoring microvascular free flaps. Level of evidence: 2 Prospective Cohort Study.